Biblical Leadership at Work Scale Development - Andrew T. Babyak (Christian Business Academy Review, 1970)
The faith at work movement began in the 1980s (Miller, 2007) and has been growing at a fast pace in recent years, but most of the work done in these fields has been religion neutral. Scholars have postulated that leadership based on the Bible would be divisive and produce negative results for the organization, but no studies have been performed to actually support those assertions (Hicks, 2002). The purpose of this study was to develop a new theory of biblical leadership and a scale that may be used to study it. A thorough review of previous research on leadership and the Bible resulted in a theory of biblical leadership that is multidimensional as it integrates the following four components: (a) relationship with God, (b) relationship with man, (c) completing the mission, and (d) organizational relationship skills. All four of the factors of the scale were studied through a principal component factor analysis and an item analysis that utilized bivariate correlations. Reliability was measured by utilizing Cronbach’s alpha (.920 for the entire scale) and a test-retest method of analyzing internal consistency. The research in this study indicated that three of the four factors of the study are valid and reliable to measure biblical leadership, but several of the items need to be examined further. There is a need to build upon this study to strengthen the scale so that a strong, reliable, and valid instrument is fully developed to enable the research necessary to examine the effectiveness and outcomes of biblical leadership.